Epidemiology of seborrheic dermatitis. (1st October 2019) - Zander, N.; Sommer, R.; Schäfer, I.; Reinert, R.; Kirsten, N.; Zyriax, B.‐C.; Maul, J.‐T.; Augustin, M.
Summary: This study from research workers in Switzerland and Germany provides new information on the skin condition seborrheic dermatitis, more specifically how common it is and whether those with the condition have other diseases (co‐morbidities). Seborrhoeic dermatitis is a common disease which shows as redness, scaling and some irritation on areas of the head such as the eyebrows, around the nostrils, behind the ears and in the scalp. The work was based on voluntary skin health checks carried out in workplaces in Germany, involving more than 160, 000 individuals. Seborrhoeic dermatitis was found in 4.6% of males and 1.4% of females and was commoner in those above the age of 35. Seborrhoeic dermatitis was commoner in those who had the following other skin conditions: folliculitis, fungal nail infections or tinea pedis (athlete's foot), rosacea, acne and psoriasis. The authors conclude that many of the other skin infections or conditions such as acne with which seborrheic dermatitis is associated, are those in which there are changes in the microbes (tiny organisms) in the skin (microbiome) and/or the production of fats or sebum on the skin surface.